Emergency medicine terminology in the United Kingdom—time to follow the trend?. Issue 2 (1st March 2001) - Reid, C; Chan, L
Abstract : Objective —To determine the frequency of use of the terms "accident and emergency" and "emergency medicine" and their derivatives in original articles in the Journal of Accident and Emergency Medicine . Methods —Hand search of all articles in the Journal of Accident and Emergency Medicine from September 1995 to July 2000, categorising the first use of terminology in each original article to describe the specialty, its departments, or their staff into either accident and emergency or emergency medicine groups. Results —There is a clear trend towards increasing use of the terms emergency medicine, emergency physician and emergency department, with decreasing use of the terms accident and emergency medicine, accident and emergency department and accident and emergency doctor, although the latter group still constitutes the majority. Conclusion —The use of emergency medicine to describe the specialty in the United Kingdom is increasing, although this may reflect the Journal's growing international standing. This trend should be taken into account in the debate over the specialty's name in this country.